PENERAPAN STRATEGI BELAJAR AKTIF TIPE INDEX CARD MACTH UNTUK MENINGKATKAN MOTIVASI BELAJAR PKn SISWA KELAS III SD NEGERI 13 KERINCI KANAN KABUPATEN SIAK - ', Supriadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the lack of student learning outcomes civics class III SD Negeri13 Kerinci Kanan Siak. This study aims to determine the learning outcome civics throughmethods index card macth class III student at SD Negeri 13 Kerinci Kanan Siak, which wasconducted over 1 month. Subjects in this study were students of class III 2015-2016 schoolyear the number of students as many as 6 people, consisting of 5 students male and 1 femalestudents. Form of research is classroom action research. The research instrument consists ofinstruments and instrument performance data collection activity observation sheet formteacher and student activity. Based on the results of research and discussion, the applicationof active learning strategies match the type of index cards can increase learning motivationthird grade students of SD Negeri 13 Kerinci Kanan Siak. Teacher activity in cycle I got aperfect score of 36 in the category, while in the second cycle got a score of 44 in the categoryof very perfect. Student motivation cycle I got an average rating of 52.8 with a high categorywhile in the second cycle gets the average value 80.6 by category high. At cycle I study thisclass action has not been successful, while the second cycle of studies have been successfulwith the indicator success of 75.0% exceeded the performance indicators that have been set.application of active learning strategies match the type of index cards can increasemotivation to learn the subjects civics third grade students of SD Negeri 13 Kerinci KananSiak acceptable